The use of CR1aa for ovine in vitro embryo production - Yulnawati .; M.A Setiadi; A Boediono (Jurnal Ilmu Ternak dan Veteriner, 2006)
The aim of this study was to investigate the capacity of CR1aa as a simple medium for maturation, fertilization and culture of ovine embryo in vitro. Oocytes were collected by slicing method in Phosphate Buffer Saline (PBS) supplemented with 5% Fetal Bovine Serum (FBS) and 100 IU/ml penicillin streptomycin. Oocytes were matured in Tissue Culture Medium (TCM)-199 as control or CR1aa as treatment medium. Both maturation medium were supplemented with 10% Fetal Bovine Serum (FBS), 10 IU/ml Follicle Stimulating Hormone (FSH), 10 IU/ml Luteinizing Hormone (LH), 1 μg/ml Estradiol and 100 IU/ml penicillin-streptomycin. Oocytes were incubated in 5% CO2 incubator, 38˚C for 24 h. Matured oocytes were fertilized in BO or CR1aa medium, supplemented with 2.5 mM caffeine benzoate and 20 mg /ml heparin. After 18 h in vitro fertilization, oocytes were cultured in TCM-199 or CR1aa medium, both supplemented with 5% FBS, 5 mg/ml insulin and 100 IU/ml penicillin streptomycin. Results showed that the highest maturation rate was found in TCM-199 medium (73.27%) and significantly different (P<0.05) from CR1aa (52.88%). Fertilization rate in CR1aa medium (67.59%) was higher (P<0.05) than in BO medium (52.94%). Furthermore, there was no significant difference (P>0.05) between cleavage rate of ovine embryos in TCM-199 and CR1aa medium (39.45% vs 50.94%). In conclusion, optimum result on ovine in vitro embryo production can be achieved from a combination of TCM-199 as maturation medium and CR1aa as fertilization and culture medium. Key Words: CR1aa, TCM-199, Embryo, Ovine